Action mechanisms of probiotics on Candida spp. and candidiasis prevention: an update - Ribeiro, F. C. [UNESP]; Rossoni, R. D. [UNESP]; de Barros, P. P. [UNESP]; Santos, J. D. [UNESP]; Fugisaki, L. R.O. [UNESP]; Leão, M. P.V.; Junqueira, J. C. [UNESP] (Oxford University Press (OUP), 2020)
Due to the high incidence of fungal infections caused by Candida species and their increasing resistance to antimicrobial treatments, alternative therapies such as probiotics have been studied. It has been show that several species of the genus Lactobacillus have anti-Candida activity, probably by direct inhibition, through competition for adhesion sites or production of secondary metabolites, and by indirect inhibition, through stimulation of the immune system of their host. However, the mechanisms of inhibition of these probiotics on Candida species have not yet been fully elucidated since this effect is related to more than one inhibition pathway. In the literature, several in vitro and in vivo studies have been developed seeking to elucidate the probiotics mechanisms of action. These studies have been focused on C. albicans inhibition assays, including analysis of antimicrobial activity, adherence capacity, biofilms formation, filamentation and interference on virulence genes, as well as assays of experimental candidiasis in invertebrate and vertebrate models. In this context, the purpose of this review was to gather different studies focused on the action mechanism of probiotic strains on Candida sp. and to discuss their impact on the candidiasis prevention.
Keywords: fungi; lactobacillus; pathogenesis; probiotic; yeasts